Upaya Meningkatkan Aktivitas dan Hasil Belajar PKn Siswa Kelas VIII-B SMPN 18 Mataram Melalui Penerapan Pendekatan Cooperative Learning Tipe Jigsaw - Pratini, Pratini (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
This study aims to determine the effectiveness of cooperative learning approach (CL) type Jigsaw in an effort to improve the activities and learning outcomes Civics Learners class VIII-B SMP Country of 18 Mataram. The benefits of this research are as a study material and findings material in the implementation the actual learning process in the classroom. For teachers to improve competence in the process learning and for learners to increase learning activities that result in increased outcomes learners learn. This research is conducted two cycles, each cycle activity is; planning, execution, observation and reflection. The final result of action in cycle II shows that results teacher observation got average score (4,18) and result of observation of student reach average score (4.22). While the result of increased learning activities of learners is the increase of the results learners achieve average score (87.15), meaning that the success indicator (> 75,00) has been exceeded. Because the success indicator has been proven that the research is successful and stopped in cycle II